1992
DOI: 10.1177/002383099200500206
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome Oxidase Inhibition: A Novel Animal Model of Alzheimer's Disease

Abstract: A profound decrease in activity of the mitochondrial enzyme cytochrome oxidase in blood platelets is a recently identified concomitant of Alzheimer's disease (AD). We investigated a possible pathogenic link between this finding and the symptoms of AD by mimicking this mitochondrial enzyme deficiency in rats. Rats were infused chronically with a selective inhibitor of cytochrome oxidase, sodium azide, or with saline delivered via subcutaneously implanted osmotic minipumps. The azide treatment impaired both spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
2
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 45 publications
2
21
2
1
Order By: Relevance
“…In addition to deficiencies in COX, deficiencies in pyruvate dehydrogenase complex (PDHC), and the a-ketoglutarate dehydrogenase complex (KGDHC) have also been reported in AD [14][15][16]. COX is complex IV of the mitochondrial respiratory electron transport chain enzyme, which interacts directly with molecular oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to deficiencies in COX, deficiencies in pyruvate dehydrogenase complex (PDHC), and the a-ketoglutarate dehydrogenase complex (KGDHC) have also been reported in AD [14][15][16]. COX is complex IV of the mitochondrial respiratory electron transport chain enzyme, which interacts directly with molecular oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…As well, activities of CO have been found to be reduced in postmortem brain tissue homogenates from AD patients (Kish et al, 1992), and in the dentate gyrus and hippocampus using histochemistry (Simonian and Hyman, 1993). Perhaps one of the most relevant studies in implicating the involvement of CO in Alzheimer's is that of Bennett et al (1992) in which it was demonstrated that treatment of rats with sodium azide, a selective inhibitor of CO, served as a model for some of the characteristics of AD. This represents a milestone in that it is not yet known whether the histopathological changes found in AD, specifically the build up of amyloid Additionally, it has been demonstrated that 3-nitropropionic acid (3-NPA), an inhibitor of succinate dehydrogenase (complex II), can model the striatal neurodegeneration found in Huntington's disease, an effect which can be reversed by the implantation of genetically altered fibroblasts which secrete high levels of Nerve Growth Factor (NGF) (Frim et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, NaN 3 (5-10 mM) was used to inhibit oxidative energy production in cultured astrocytes 14,29,30 and systemically in animals. [31][32][33][34][35] Other recent studies using cell culture and tissue-based assays have also relied on NaN 3 to generate chemical hypoxia. 36,37 In addition to cytochrome oxidase, NaN 3 also inhibits nucleoside triphosphate diphosphohydrolase, an ecto-diphosphohydralase that hydrolyzes nucleosides extracellularly at pH 8.…”
Section: Metabolic Inhibitorsmentioning
confidence: 99%